Truth and Reconciliation in Post-Conflict Ukraine - Everett Judas (Politics in Central Europe)
This article deals with the effectiveness of a potential Truth and Reconciliation Commission in the case of Ukraine. A framework of common factors, which can either influence the effectiveness of a commission positively or negatively, is provided by analysing the cases of TRCs which were very successful and by considering the factors which contributed to their success, as well as the less successful cases and the factors which contributed to their lack of success. Subsequently, the previous ways truth and reconciliation have been addressed in the case of Ukraine is explored before the potential effectiveness of a future TRC in Ukraine is considered. The future of the conflict remains in the balance, as does the future of the post-conflict environment. However, a TRC in the Ukrainian case is highly possible as positive factors such as a broader transitional justice strategy and international support for post conflict reconstruction are important. This is also true for the negative factors, such as potential Western war fatigue or weariness, a potentially disengaged and/or distrustful society, especially if the TRC fails to be politically independent. Much will depend on the staff of the TRC and the procedures they follow.